Racism and anti-racism in world perspective - Bowser, Benjamin P. 1946- (Sage Series on Race and Ethnic Relations, 1995)
Americans who study racism and the movements to counteract racism tend to look only at the U.S. situation in their attempts to understand the two phenomena. However, focusing only on the familiar and the national makes it very difficult to see how racism in the United States has been defined by our culture and history - and how it can be changed. For these reasons, Racism and Anti-Racism in World Perspective, edited by Benjamin P. Bowser, is a unique and valuable resource for students and scholars of race relations. The book's contributors come from a wide range of backgrounds, including anthropology, classics, sociology, political science, communications, and history. They examine racism and anti-racism through the historical and cultural lenses of different world settings, including Europe, South America, Africa, America, and the Caribbean. This progressive approach changes and expands the framework through which we understand the genesis and dynamics of racism and antiracism.